Making a diagnosis of periodic fever syndrome: Experience from a single tertiary centre. (9th September 2021) - McNaughton, Peter; Willcocks, Sophie; Lum, Su Han; Whitehead, Ben; Peake, Jane; Preece, Kahn
Abstract : Aim: This study aims to evaluate the utility of genetic testing of patients diagnosed with periodic fever syndromes and to assess the validity of existing scoring criteria. Methods: This study retrospectively reviewed the clinical history of patients diagnosed with periodic fever syndromes at Queensland Children's Hospital between November 2014 and June 2018. Results: Forty‐three patients were diagnosed with periodic fever syndromes. Diagnoses in the cohort included periodic fever, adenitis, pharyngitis and aphthous stomatitis (10), tumour necrosis factor receptor‐associated periodic syndrome (9), cryopyrin‐associated periodic syndrome (6), mevalonate kinase deficiency (4) while 14 remained unspecified. No presenting symptoms were uniquely associated with any particular diagnosis. Genetic testing of between 1 and 26 genes was performed in 26 (60%) patients. Two (7.7%) patients had pathogenic variants identified. Variants of uncertain significance which were insufficient to confirm a monogenic disorder were identified in a further 7 (27%) patients. The Eurofever classification criteria correlated with clinical diagnosis for patients diagnosed with cryopyrin‐associated periodic syndrome ( P = 0.046) and tumour necrosis factor receptor‐associated periodic syndrome ( P = 0.025) but not for patients diagnosed with mevalonate kinase deficiency ( P = 0.47); however, the Eurofever classification criteria were often positive for more than one diagnosis in these patients. Conclusion: The European classification criteria can form a potentially useful tool to guide diagnosis; however, clinical judgement remains essential, because the score is often positive for multiple diagnoses. The diagnostic yield of genetic testing in this cohort was low and genetic testing may be more useful to confirm a strong clinical suspicion than to clarify a diagnosis for patients with less clear symptoms.